Effect Of Carbon Nanotube On Microstructure And Hardness Of Sn96.5Ag3.0Cu0.5 Solder For Microelectronic Packaging - Omar, Ghazali; Ahmad, Intan Fatihah; A Hamid, Husna; Salim, Mohd Azli (Praise Worthy Prize, 2021)
This study investigated the SAC305 solder alloy’s performance after being reinforced with 0.01, 0.02, 0.03, and 0.04 wt.% of CNT. The performance of reinforced solders was evaluated based on their microstructure and hardness. The reinforced solder’s microstructure was observed using Scanning Electron Microscope (SEM) equipped with Energy Dispersive X-ray (EDX). The indentation of reinforced solder was carried out to identify its mechanical properties. According to the P-h graph, the reinforced solder becomes harder as the wt.% of CNT incorporated into the solder increases. The CNT particles were observed to be distributed along the grain boundary and suppressed the solder’s crystal nucleation through the pinning effect process. Compared to SAC 305 solder alloy, the reinforced solder has better performance in terms of mechanical properties. Copyright © 2021 Praise Worthy Prize S.r.l.-All rights reserved.